Antibody and cytokine serum levels in patients subjected to anti-rabies prophylaxis with serum-vaccination - J. A. Ayres; B. Barraviera; S. A. Calvi; N. R. Carvalho; M. T. S. Peraçoli (Journal of Venomous Animals and Toxins including Tropical Diseases, 2006)
Rabies is considered a fatal disease once clinical symptoms have developed. The aim of this study was to evaluate epidemiological aspects and immune response in patients attacked by domestic and wild animals and subjected to post-exposure rabies treatment with equine serum and associated vaccine. Thirty-three patients were evaluated; they were between 13 and 65 years old, 75.8% were male and 24.2% female, and from the Botucatu neighborhood. Twenty healthy control individuals with the same age range were also studied. Specific antibodies to equine immunoglobulins and IFN-gamma, IL-2, IL-4, and IL-10 production were evaluated by ELISA. IgM, IgE, IgG and subclasses, and rabies virus antibodies serum levels were determined by nephelometry and seroneutralization methods, respectively. No anaphylactic or serum sickness allergic reactions were observed in patients after treatment. Anti-equine IgG levels were significantly higher than those of IgM after 14 and 28 days of treatment. Protective antibodies to rabies virus > 0.5 UI/ml were detected in 84.6% and 75% of patients at days 14 and 28, respectively. IFN-gamma, IL-2 and IL-10 levels in patients before and 48h after treatment were significantly higher than in controls suggesting that both Th1 and Th2 cells were activated in the patients. Serum IgM levels were higher at day 14, and IgG2 and IgE levels were higher at day 28 of treatment. These results suggest that post-exposure rabies treatment in humans induces significant alterations in patient immune response characterized by increased levels of cytokines, serum levels of specific rabies virus antibodies, and the equine serum components employed in the treatment.